GAINING OIL AND GAS INDEPENDENCE IN THE REPUBLIC OF UZBEKISTAN IS THE BASIS OF A PROSPEROUS AND PROSPEROUS LIFE (Academia Science Repository, 2023)
In this article, the gaining of oil and gas independence in the Republic of Uzbekistan during the years of independence, reforms implemented in the field and their results, institutional changes in the field are subjected to a historical analysis.